Functional Exercise and Physical Fitness Post Stroke: The Importance of Exercise Maintenance for Motor Control and Physical Fitness after Stroke. (18th January 2012) - Langhammer Langhammer, Birgitta Birgitta; Lindmark Lindmark, Birgitta Birgitta
Abstract : It is argued that all stroke patients, indifferent of disability, have the same possibility to improve with training. The aim of the study was to follow and register functional improvements in two groups with different functional capacities at baseline for a period of 36 months. Stroke patients were recruited and divided into groups related to their functional status at baseline. During the acute rehabilitation, both groups received functional task-oriented training, followed by regular self- or therapeutic driven training the first year after stroke and varied exercise patterns the following 24 months. The participants were tested on admission, and at three, six, twelve, and thirty-six months after the onset of stroke. Both groups improved functional activity up to six months which then stabilized up to twelve months to decline somewhat at thirty-six months after stroke. Change scores indicate a greater potential for rehabilitation in the MAS ≤35 in relation to group MAS >35 although the functional capacity was higher in the latter. This indicates the importance of maintaining exercise and training for all persons after stroke.